THE ROLE OF INTERNATIONAL LAW IN SHAPING MIGRATION POLICIES: A COMPARATIVE STUDY OF UZBEKISTAN AND REGIONAL TRENDS IN CENTRAL ASIA - Asadov Davlatbek (International Journal of Business, Law and Political Science, 2024)
Background: The increasing complexity of migration dynamics in Central Asia necessitates a comprehensive understanding of the role of international law in shaping national policies. Specific Background: Uzbekistan, as a key player in the region, provides a unique case study for examining the interplay between international legal frameworks and national migration policies, particularly in the context of its relationships with neighboring Kazakhstan, Kyrgyzstan, Tajikistan, and Turkmenistan. Knowledge Gap: Despite the significance of international conventions and treaties, there remains a paucity of research addressing how these instruments specifically influence the migration policies of Central Asian countries. Aims: This article aims to analyze the alignment of Uzbekistan’s migration policies with international standards and to conduct a comparative assessment with those of its Central Asian neighbors. Results: The findings reveal that while Uzbekistan has made strides in adopting international norms, substantial discrepancies persist between its policies and those of neighboring states, highlighting varying degrees of compliance and implementation challenges. Novelty: This study contributes to the existing literature by offering a nuanced comparative analysis that integrates international law with national migration policies in Central Asia, a region often overlooked in global migration discourse. Implications: The research underscores the dual role of international law as both a challenge and an opportunity for the development of coherent migration policies in Central Asia, suggesting pathways for enhanced regional cooperation and compliance with international standards.